Developmental origins and evolution of pallial cell types and structures in birds - data - Zaremba, Bastienne; Fallahshahroudi, Amir; Schneider, Céline; Schmidt, Julia; Sarropoulos, Ioannis; Leushkin, Evgeny; Berki, Bianka; Van Poucke, Enya; Jensen, Per; Senovilla-Ganzo, Rodrigo; Hervas Sotomayor, Francisca; Trost, Nils; et al. (Universität, 2024)
The advanced cognitive abilities of birds rival those of mammals and have been attributed to evolutionary innovations in the pallium. However, a comprehensive cellular characterization of this brain region in birds has been lacking. We scrutinized the structures, cell types and evolutionary origins of the avian pallium based on single-cell and spatial transcriptomics atlases for the adult and developing chicken, and comparisons to corresponding data from mammals and non-avian reptiles. We found that the avian pallium shares most inhibitory neuron types with other amniotes. While excitatory neuron repertoires in the (medial) hippocampal formation show high conservation, they substantially diverged in other pallial regions during avian evolution, defining novel structures like the avian-specific (dorsal) hyperpallium, whose neuronal gene expression identities partly converge during late development with those of the (ventral) nidopallium. Our work also unveils the evolutionary relationships of pallial structures across amniotes, like the previously unknown homology between avian (lateral) mesopallial and mammalian deep layer cortical neurons.
Gesehen am 02.05.2024
Keywords: Forschungsdaten; Datenbank